ANALISIS KETERKAITAN SEKTOR AGROINDUSTRI TERHADAP PEREKONOMIAN DI PROVINSI LAMPUNG - Rendy Oktaliando; Agus Hudoyo; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This research aims to find out the forward linkage and backward linkage of agroindustry sector on economyin Lampung Province. This research used data from the industries of oil/fat, sugar, rubber and plastic, andcoffee. The analysis method used in this research was Input-Output Analysis. The results showed that theforward linkage index of oil/fat industry, sugar industry, rubber and plastic goods industry, and coffeeindustry were 0.91; 1.15; 0.88; and 0.80. The average of the four values was 0.94. The backward linkageindex of oil/fat industry, sugar industry, rubber and plastic goods industry, and coffee industry were 0.72;0.91; 0.86; and 0.75 , with the average value was 0.81. The forward linkage index and backward linkageindex of agroindustry sector were less than 1. It meant that agroindustry sector had low linkage with othersectors on economy in Lampung Province.